Estimation of the IC to CG Ratio Using JEM‐GLIMS and Ground‐Based Lightning Network Data. Issue 23 (30th November 2020) - Bandholnopparat, K.; Sato, M.; Adachi, T.; Ushio, T.; Takahashi, Y.
Abstract: The occurrence ratio of intracloud (IC) to cloud‐to‐ground (CG) discharges, which is denoted by Z ‐ratio, is the crucial parameter for the studies on the global electric circuit. However, the latitudinal and regional dependences of Z ‐ratio are not fully clarified. Therefore, using optical data obtained by the Global Lightning and Sprite Measurements on Japanese Experiment Module (JEM‐GLIMS), we distinguished the lightning discharge type, that is, IC, positive CG (+CG), and negative CG (−CG) discharges, and statistically estimated the Z ‐ratio. We analyzed 8, 354 lightning events that obtained by JEM‐GLIMS observation and succeeded in identifying 4, 431 IC discharges, 597 +CG discharges, and 3, 326 −CG discharges. From this result, we calculated the Z ‐ratio over many regions around the world and estimated its latitudinal and regional dependences. It is found that the Z ‐ratio over the continental area is larger than the oceanic area. We also found that the Z ‐ratio significantly decreases with the latitude, which is generally comparable to the results shown in the previous studies. The estimated Z ‐ratio varies from 2.9–0.29 from the equator to 50° latitude, and the global mean value is 1.6. The regional dependence of Z ‐ratio derived from this study can be combined with the CG lightning data provided by the ground‐based lightning detection networks to estimate the occurrence number of IC discharges. Then, the occurrence number of both IC and CG discharges can be used for calculating a more accurate estimation of the total lightning currents in the global electric circuit. Key Points: A new method for classifying the lightning discharge type has been developed using JEM‐GLIMS and the ground‐based lightning data Lightning flashes obtained by JEM‐GLIMS observation were used to study the geographic distribution of Z ‐ratio The relationship between Z ‐ratio and latitude was found, in which it has a good agreement compared with previous studies